Synthesis of a new 2-prenylated quinoline as potential drug for metabolic syndrome with pan-PPAR activity and anti-inflammatory effects - Villarroel Vicente, Carlos (2024)
We have previously reported the total synthesis and structure–activity relationships (SAR) of 2-prenylated benzopyrans with PPAR agonist activity. Herein, we have described the synthesis and PPAR activity of 2-prenylated benzopyrans and 2-prenylated quinolines. The benzopyran nucleus was generated via enamine-catalyzed Kabbe condensation, and the quinoline nucleus via Friedländer condensation. Results demonstrated that both benzopyran (5a) and quinoline (4b) derivatives bearing a γ,δ-unsaturated ester displayed a pan-PPAR agonism. They were full PPARα agonists, but showed different preferences for PPARγ and PPARβ/δ activation. It was noteworthy that quinoline 4b displayed full hPPARα activation (2-fold than WY-14,643), weak PPARβ/δ and partial PPARγ activation. In addition, quinoline 4b showed anti-inflammatory effects on macrophages by reducing LPS-induced expression of both MCP-1 and IL-6. Therefore, 4b emerges as a first-in-class promising hit compound for the development of potential therapeutics aimed at treating metabolic syndrome, metabolic dysfunction-associated fatty liver disease (MAFLD), and its associated cardiovascular comorbidities.